A functional metagenomics study of soil carbon and nitrogen degradation networks and limiting factors on the Tibetan plateau - Yang, Chong; Zhang, Hong; Zhao, Xinquan; Liu, Pan; Wang, Lushan; Wang, Wenying (Frontiers in Microbiology, 2023)
The Three-River Source Nature Reserve is located in the core area of the Qinghai-Tibetan Plateau, with the alpine swamp, meadow and steppe as the main ecosystem types. However, the microbial communities in these alpine ecosystems, and their carbon and nitrogen degrading metabolic networks and limiting factors remain unclear. We sequenced the diversity of bacteria and fungi in alpine swamps, meadows, steppes, and their degraded and artificially restored ecosystems and analyzed soil environmental conditions. The results indicated that moisture content had a greater influence on soil microbial community structure compared to degradation and restoration. Proteobacteria dominated in high moisture alpine swamps and alpine meadows, while Actinobacteria dominated in low moisture alpine steppes and artificial grasslands. A metabolic network analysis of carbon and nitrogen degradation and transformation using metagenomic sequencing revealed that plateau microorganisms lacked comprehensive and efficient enzyme systems to degrade organic carbon, nitrogen, and other biological macromolecules, so that the short-term degradation of alpine vegetation had no effect on the basic composition of soil microbial community. Correlation analysis found that nitrogen fixation was strong in meadows with high moisture content, and their key nitrogen-fixing enzymes were significantly related to Sphingomonas. Denitrification metabolism was enhanced in water-deficient habitats, and the key enzyme, nitrous oxide reductase, was significantly related to Phycicoccus and accelerated the loss of nitrogen. Furthermore, Bacillus contained a large number of amylases (GH13 and GH15) and proteases (S8, S11, S26, and M24) which may promote the efficient degradation of organic carbon and nitrogen in artificially restored grasslands. This study illustrated the irrecoverability of meadow degradation and offered fundamental information for altering microbial communities to restore alpine ecosystems.